Host-Pathogen Interaction as a Novel Target for Host-Directed Therapies in Tuberculosis - Abreu, Rodrigo; Giri, Pramod; Quinn, Fred (Frontiers in Immunology, 2020)
Tuberculosis (TB) has been a transmittable human disease for at least 70,000 years, and M. tuberculosis is again the number one cause of death worldwide due to a single infectious agent. The intense 6- to 10-month process of multi-drug treatment, combined with the adverse side effects that can run the spectrum from gastrointestinal disturbances to liver toxicity or peripheral neuropathy are major obstacles to patient compliance and therapy completion. The consequent increase in multidrug resistant TB (MDR-TB) and extensively drug resistant TB (XDR-TB) cases requires that we increase our arsenal of effective drugs and calls for the development of novel therapeutic approaches. Over the millennia, host and pathogen have evolved mechanisms and relationships that greatly influence the outcome of infection. Understanding these evolutionary interactions and their impact on bacterial clearance or host pathology will lead the way towards rational development of new therapeutics that favor a host protective response. These host-directed therapies have recently demonstrated promising results against M. tuberculosis, enhancing the cumulative effects of currently available anti-mycobacterial drugs or directly decreasing bacterial replication. Here we review the host-pathogen interactions during M. tuberculosis infection, describe how M. tuberculosis bacilli modulate and evade the host immune system, and the currently available host-directed therapies that target these bacterial virulence mechanisms. Rather than provide an exhaustive description of M. tuberculosis virulence factors, which falls outside the scope of this review, we will instead focus on the host-pathogen interactions that lead to increased bacterial growth or host immune evasion, and which can be modulated by existing host-directed drugs. The host-directed therapies reviewed here may not be sufficient to contain and clear M. tuberculosis bacilli in an active TB patient, but might increase the effect of currently available anti-mycobacterial drugs, and give the immune system the extra support it needs to most effectively contain an infection.